2022
DOI: 10.22207/jpam.16.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Potential Risk Factors of Hepatitis E Virus among Pregnant Women in Khartoum, Sudan

Abstract: Although hepatitis E virus (HEV) infection has been widely understood as a public health concern in pregnant females, it is sometimes overlooked because of unusual observations of hepatitis E-induced complications during pregnancy. The objective of this descriptive cross-sectional study was to find out how frequent Hepatitis E virus infection is in pregnant women in Sudan. Blood samples were collected from pregnant women (n = 90) attending Khartoum North Hospital from February to December 2019. The specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…19 Another similar study from China, 6.0% of pregnant women were positive for anti-HEV IgG antibody, 0.3% were anti-HEV IgM antibody positive and 0.3% were positive for both anti-HEV IgG and anti-HEV IgM antibodies, which was well in concordance with our study. 20 Mustafa et al 21 in their study reported high prevalence of 40% for IgG antibodies and 6% positive for IgM antibodies, access to healthy food and clean water is almost impossible for study participants. Such conditions provide a great environment for disease.…”
Section: Discussionmentioning
confidence: 91%
“…19 Another similar study from China, 6.0% of pregnant women were positive for anti-HEV IgG antibody, 0.3% were anti-HEV IgM antibody positive and 0.3% were positive for both anti-HEV IgG and anti-HEV IgM antibodies, which was well in concordance with our study. 20 Mustafa et al 21 in their study reported high prevalence of 40% for IgG antibodies and 6% positive for IgM antibodies, access to healthy food and clean water is almost impossible for study participants. Such conditions provide a great environment for disease.…”
Section: Discussionmentioning
confidence: 91%
“…Hospital-based research conducted during a Delhi outbreak found that HEV infection during pregnancy was linked to perinatal death, stillbirth, or miscarriage in 56% of cases. According to a recent study, antenatal maternal deaths are often linked to additional fetal deaths, and in developing countries, HEV infection may cause 2400-3000 stillbirths each year [45]. Pregnant women with HEV infection have a high risk of preterm delivery and poor neonatal survival rates.…”
Section: Incidence Rate Of Hev In Pregnant Femalesmentioning
confidence: 99%